2017
DOI: 10.1007/s00441-017-2689-6
|View full text |Cite
|
Sign up to set email alerts
|

Procollagen C-proteinase enhancer 1 (PCPE-1) functions as an anti-angiogenic factor and enhances epithelial recovery in injured cornea

Abstract: Procollagen C-proteinase enhancer 1 (PCPE-1) has been characterized as a protein capable of enhancing the activity of bone morphogenetic protein 1/tolloid-like proteinases (BTPs) in the biosynthetic processing of C-propeptides from procollagens I–III. This processing step is thought necessary to the formation of collagen I–III monomers capable of forming fibrils. Thus, PCPE-1 is predicted to play an important role in scarring, as scar tissue is predominantly composed of fibrillar collagen. Corneal scarring is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…16 Recent studies have also shown that PCPE-1 is associated with corneal scarring and dermal scar formation. 17,18 Our review of the literature revealed no studies reporting the relationship between CKD and PCPE-1. PCPE-1 levels in patients with CKD in our study were significantly higher than in the healthy controls.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…16 Recent studies have also shown that PCPE-1 is associated with corneal scarring and dermal scar formation. 17,18 Our review of the literature revealed no studies reporting the relationship between CKD and PCPE-1. PCPE-1 levels in patients with CKD in our study were significantly higher than in the healthy controls.…”
Section: Discussionmentioning
confidence: 92%
“…Kessler‐Icekson et al showed an association between PCPE‐1 and aldosterone‐mediated fibrosis in heart tissue during remodelling following acute myocardial infarction in rats . Recent studies have also shown that PCPE‐1 is associated with corneal scarring and dermal scar formation . Our review of the literature revealed no studies reporting the relationship between CKD and PCPE‐1.…”
Section: Discussionmentioning
confidence: 99%
“…The link between PCPE-1 up-regulation and fibrosis has already been demonstrated in several organs such as liver, muscle, skin or cornea [25][26][27][28] . Regarding cardiac fibrosis, PCPE-1 was found to be increased in endomyocardial biopsies from a cohort of 28 patients suffering from aortic valve stenosis 29 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the expression of PCOLCE positively correlates with muscle and liver fibrosis 16. A PCOLCE deficiency contributes to deficient corneal repair 17. Mutated PABPN1 binds to PCOLCE and entraps it within the nuclear compartment, leading to oculopharyngeal muscular dystrophy 18.…”
Section: Introductionmentioning
confidence: 99%